The modulatory effect of electrical stimulation on the excitability of the corticospinal tract varies according to the type of muscle contraction being performed - Saito, Kei; Sugawara, Kenichi; Miyaguchi, Shota; Matsumoto, Takuya; Kirimoto, Hikari; Tamaki, Hiroyuki; Onishi, Hideaki (Frontiers in Human Neuroscience, 2014)
Afferent input caused by electrical stimulation of a peripheral nerve increases corticospinal excitability during voluntary contractions, indicating that proprioceptive sensory input arriving at the cortex plays a fundamental role in modulating corticospinal excitability. The purpose of this study was to investigate whether the effect of electrical stimulation on the corticospinal excitability varies according to the type of muscle contraction being performed. Motor-evoked potentials (MEPs) were elicited by transcranial magnetic stimulation during a shortening contraction, an isometric contraction, or no contraction of the first dorsal interosseous muscle. In some trials, electrical stimulation of the ulnar nerve was performed at 110% of the sensory threshold or 110% of the motor threshold prior to transcranial magnetic stimulation. Electrical stimulation involved either a train of 50 pulses at 10 Hz or a single pulse. Shortening contraction with the train of electrical stimuli significantly increased MEP amplitudes, and the increase was dependent on the type of stimulation. Isometric contraction with the train of electrical stimuli and electrical stimulation without voluntary contraction did not affect MEP amplitudes. A single pulse of electrical stimulation did not affect MEP amplitudes in any condition. Thus, electrical-stimulation-induced modulation of corticospinal excitability varied according to the type of muscle contraction performed and the type of stimulation. These results show that the type of contraction should be considered when using electrical stimulation for rehabilitation in patients with central nervous system lesions.